MATLAB Based PCM Modeling and Simulation - Yongchao Jin; Hong Liang; Weiwei Feng; Qiong Wang (Institute of Advanced Engineering and Science, 2013)
PCM is the key technology of digital communication, and has especially been widely used in the optical fiber communication, digital microwave communication, satellite communication. Modeling PCM communication systems with the pulse code system by programming, and conduct computer simulation by MATLAB, to analysis performance of the linear PCM and logarithmic PCM. DOI: http://dx.doi.org/10.11591/telkomnika.v11i10.3430